Influence of Left Atrial Appendage Amputation on Natriuretic Peptides—A Randomized Controlled Trial - Grieshaber, Philippe; Arneth, Borros; Steinsberger, Ferdinand; Niemann, Bernd; Oswald, Irina; Renz, Harald; Böning, Andreas (The Thoracic and Cardiovascular Surgeon, 2019)
Background Closure or amputation of the left atrial appendage (LAA) is a common therapy for atrial fibrillation (AF). As the LAA is a hormone-producing organ, however, amputation is still somewhat controversial. We examined patients after surgical AF therapy with or without LAA amputation to determine the influence of LAA amputation on pro-atrial natriuretic peptide (proANP) and B-type natriuretic peptide (BNP) plasma levels and on clinical severity of heart failure.Methods Twenty-one consecutive patients were prospectively randomized to either undergo LAA amputation (n = 10) or no LAA amputation (n = 11) between 05/2015 and 10/2015. All patients underwent coronary and/or valve surgery and concomitant AF surgery with either cryoablation (n = 3) or radio frequency ablation (n = 17). ProANP and BNP levels were measured preoperatively and until 800 days postoperatively.Results Baseline proANP values were comparable between the groups (without LAA amputation: 4.2 ± 2.1 nmol/L, with LAA amputation: 5.6 ± 3.6 nmol/L). Postoperatively, proANP levels rose markedly in both groups. Even after LAA amputation, proANP levels remained elevated for 7 days postoperatively but fell to baseline levels at day 31 and remained on baseline level at 800 days postoperatively. ProANP levels in the LAA amputation group (5.8–9.7 nmol/L) were not significantly lower than in the group without LAA amputation (9.2–14.1 nmol/L; p = 0.357). BNP levels also rose after surgery in both groups until day 7. At 800 days after surgery, BNP levels were back at baseline levels in both groups. Clinical follow-up at 2 years postoperatively showed no difference in heart failure symptoms or need for heart failure medication between the groups.Conclusion In contrast to commonly held beliefs about the endocrine and reservoir functions of the LAA, there seems to be no clinically relevant detrimental effect of LAA amputation on natriuretic peptide levels and severity of heart failure until up to 2 years postoperatively.
Keywords: arrhythmia therapy; heart failure; molecular biology; physiology